Analisis Meningkatkan Kemampuan Digital Guru Melalui Metode Knowshare pada Masa Pandemic Covid -19 di Komed Depok - Nurkaidah Nurkaidah; Dwi Kartika Susantia (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2023)
The research aims to (1) describe the increase in the digital skills of Komed Depok teachers using the Knowshare method during the Covid-19 Pandemic, (2) Analyze the effect of increasing the digital abilities of Komed Depok teachers with the knowshare method during the Covid-19 pandemic. Using quantitative. The sample is 47 teachers from the c community in Depok. Respondents from various levels of kindergarten, elementary and high school. public and private schools. 80% private and 20% state. Female respondents 44 (93.6%) male respondents 3 (6.4 %). The results of the analysis of teachers' digital abilities before and after participating in KOMED: A. 21 people, 47.18% of respondents have increased digital skills. Comparison of teachers' digital abilities and pedagogical and professional competencies is increasing. B. Teachers whose ability remains at 46.9% as before, there is no increase and the intensity of following Shareknow komed is also high at 93.18%. C. komed participants with digital skills decreased by 6.1% because the intensity of participating in komed knowshare was low by 62.50%. Thus, it can be concluded that there is a positive and significant effect between increasing the digital skills of Komed Depok teachers and the knowshare method during the Covid-19 pandemic. Research on the analysis of increasing the digital skills of Komed Depok teachers using the knowshare method during the Covid-19 pandemic can reveal new information regarding the factors for increasing the digital skills of Komed Depok teachers using the knowshare method during the Covid-19 pandemic. The method used is purposive random sampling, the use of questionnaires and descriptive analysis. Keywords: 1, Teacher digitization ability 2; KnowShare Method 3; Covid-19 pandemic Analisis Meningkatkan Kemampuan Digital Guru Melalui Metode Knowshare Pada Masa Pandemic Covid -19 Di Komed Depok Nurkaidah1, Dwi Kartika Susantia,2 1 Program Studi PPKn STKIP Arrahmaniyah Depok 2 Pendidikan Biologi STKIP Arrahmaniyah Depok nurkaidah2203@gmail.com, kartika.stkiparrahmaniyah@gmail.com ABSTRACT The research aims to (1) describe the increase in the digital skills of Komed Depok teachers using the Knowshare method during the Covid-19 Pandemic, (2) Analyze the effect of increasing the digital abilities of Komed Depok teachers with the knowshare method during the Covid-19 pandemic. Using quantitative. The sample is 47 teachers from the c community in Depok. Respondents from various levels of kindergarten, elementary and high school. public and private schools. 80% private and 20% state. Female respondents 44 (93.6%) male respondents 3 (6.4 %). The results of the analysis of teachers' digital abilities before and after participating in KOMED: A. 21 people, 47.18% of respondents have increased digital skills. Comparison of teachers' digital abilities and pedagogical and professional competencies is increasing. B. Teachers whose ability remains at 46.9% as before, there is no increase and the intensity of following Shareknow komed is also high at 93.18%. C. komed participants with digital skills decreased by 6.1% because the intensity of participating in komed knowshare was low by 62.50%. Thus, it can be concluded that there is a positive and significant effect between increasing the digital skills of Komed Depok teachers and the knowshare method during the Covid-19 pandemic. Research on the analysis of increasing the digital skills of Komed Depok teachers using the knowshare method during the Covid-19 pandemic can reveal new information regarding the factors for increasing the digital skills of Komed Depok teachers using the knowshare method during the Covid-19 pandemic. The method used is purposive random sampling, the use of questionnaires and descriptive analysis. Keywords: Teacher digitization ability, KnowShare Method , Covid-19 pandemic